DEVELOPMENT OF ANDROID-BASED AUGMENTED REALITY TALKING AS BIOLOGY LEARNING MEDIA IN PLANT ANATOMY CONCEPT - Renaldy Rachman Septian; Purwati Kuswarini Suprapto; Ryan Ardiansyah (Universitas Negeri Medan, 2022)
This research aims to develop a biology learning media using Augmented Reality technology with added audio features for material explanations, and to test its suitability among students and biology teachers. The development research follows the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. Data were collected through interviews and questionnaire distribution, while data analysis was conducted using descriptive statistical techniques. This study resulted in a product called Talking Augmented Reality (TAR) for plant anatomy, an application designed for smartphones with the Android operating system. The application obtained a satisfactory level of validity in media validation and highly satisfactory results in material validation. The TAR application for plant anatomy was deemed highly suitable in the evaluation conducted with a small group of users consisting of 14 students and one biology teacher. It serves as an alternative learning media for studying plant anatomy concepts and effectively aids the biology learning process.